The Effect of The Use of Augmented Reality Learning Media on Students' Learning Interest in Mathematics Learning in Grade V at State Elementary School 1 Darma (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to obtain information about the effect of the use of Augmented Reality learning media on students' interest in learning mathematics in grade V in Elementary Schools, so that empirical information is obtained. A quantitative approach with Quasi Experimental Design with Nonequivalent Control Group Design was chosen as the method in this study. This method is used with an initial test (pretest) to determine the initial conditions, after which a final test (posttest) is given. After testing the hypothesis, the Paired Sample T Test obtained a sig. 0.001